2021
DOI: 10.1177/21582440211065770
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Potential of Agri-Food Trade Using the Stochastic Frontier Gravity Model: Empirical Evidence From Nigeria

Abstract: Considering the importance of agri-food exports for Nigeria in the face of dwindling revenue from its oil exports. Therefore, this study provides empirical insights on the determinants and potential of agri-food exports from Nigeria to 70 major trading countries between 1995 and 2019 by applying a Stochastic Frontier Analysis (SFA) on a gravity model. We also estimate a variety of techniques, including the fixed effects, Ordinary Least Square (OLS), Pseudo Poisson Maximum Likelihood (PPML), and Heckman models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 58 publications
1
8
0
2
Order By: Relevance
“…The gravity model has been widely used in the field of trade performance (Abbas et al, 2015; Abdullahi, Huo et al, 2021). Apart from the basic variables (GDP and distance) (Abdullahi, Shahriar et al, 2021; Abdullahi et al, 2022), this study also includes additional variables such as trade agreements, exchange rates, language, and common borders.…”
Section: Methodsmentioning
confidence: 99%
“…The gravity model has been widely used in the field of trade performance (Abbas et al, 2015; Abdullahi, Huo et al, 2021). Apart from the basic variables (GDP and distance) (Abdullahi, Shahriar et al, 2021; Abdullahi et al, 2022), this study also includes additional variables such as trade agreements, exchange rates, language, and common borders.…”
Section: Methodsmentioning
confidence: 99%
“…The stochastic frontier gravity model is applied on a dataset including 35 countries during 2009–2017 by [ 33 ], the results indicated that the trade resistance of China’s export to countries along the Belt and Road has increased over time, while there is still huge trade potential at various industries. [ 34 ] provided empirical insights on the determinants and potential of agri-food exports from Nigeria to 70 major trading countries between 1995 and 2019 by applying a Stochastic Frontier Analysis on a gravity model. [ 35 ] aimed to examine the key determinants and efficiency of China’s agricultural exports with its 114 importing countries by applying the Stochastic Frontier Analysis on an augmented gravity model for the period of 2000–2019.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their findings as obtained from the extended gravity model and SFA revealed GDP, exchange rate and new member states negatively affect agri-food exports to EU countries. Similarly [ 1 ], report that economic size (GDP), ECOWAS membership, EU membership, importers’ population, and contiguity promote agri-food exports to 70 of Nigeria’s major trading partners. Border countries and larger economies have been found to remain the potential markets for Nigeria’s agri-food exports.…”
Section: Literature Reviewmentioning
confidence: 99%